Persistence of aggression into adulthood in detained adolescent females - Anne A. Krabbendam; Lucres M.C. Jansen; Peter M. van de Ven; Elsa van der Molen; Theo A.H. Doreleijers; Robert R.J.M. Vermeiren (Comprehensive Psychiatry, 2014)
Objective: Although detained adolescent females show high rates of severe aggression, we know little about the long-term impact of this risk-behavior. Furthermore, qualitative differences in aggression between males and females argue for gender specific research. In contrast to males, females display aggressive acts more often towards themselves (inward aggression; self harm behavior) than towards others (outward aggression). Therefore, this prospective study investigated the prevalence and predictive validity of different types of aggression in detained adolescent females. Method: Participants were 139 adolescent females (mean age 20.1) assessed at start of detention and 5 years later. Both inward and outward aggression subtypes were assessed twice using standardized instruments. Mutual relations over time were analyzed by means of structural equation modeling. Results: High levels of all types of aggression were found repeatedly, suggesting substantial persistence over time. While inward aggression predicted both inward and outward aggression at follow-up, outward aggression was related to outward aggression only. Furthermore, the covert form of outward aggression only, and not the overt subtype, predicted outward aggression 5 years later. Conclusions: This study suggests that aggression in detained adolescent females does not fade away, and should thus be given substantial clinical attention. In assessment, focus should also be on inward and covert subtypes. Further research should explore the necessity of developing gender-specific diagnostic instruments, treatment modules and risk assessment tools. When replicated, our findings may also bear implications for the classification of behavior disorders in adolescent females.